A new species of the genus Fredius Pretzmann, 1967 (Decapoda: Brachyura: Pseudothelphusidae) from Brazil, with comments on the southerly distribution of the family - Martins, Carlos A. M.; Nascimento, Whandenson M. Do; Santos, Livanio C. Dos; Magalhães, Célio; Pinheiro, Allysson P. (Zootaxa, 2021)
A new species of pseudothelphusid crab of the tribe Kingsleyini Ortmann, 1897, from the southern Amazon region in the state of Rondônia, Brazil, is described and illustrated. Fredius avilai n. sp. can be readily distinguished from its congeners by the following characters of the male first gonopod: mesial lobe elongated, convoluted, proximal portion directed laterally, distal portion sharply recurved in abdominal direction; marginal process rounded, not projected over distal opening of spermatic channel, merging with distal portion of abdominal surface after a shallow depression; lateral suture well demarcated along mesoabdominal surface of stem, distal portion directed inwards. The assignment of the new species to the genus Fredius Pretzmann, 1967 and its affinities with another closed related species are discussed.